The Asymmetric Impact of Health Expenditure, Bottom Decile Income, and Trade Openness on BRICS Health Indicators - Дхиани Мехта; Валентина Валерьевна Дербенева (Экономика региона, 2025)
Amid growing concerns about widening health inequities and the complex interaction of socioeconomic determinants, the problem of improving health outcomes in emerging economies—particularly within BRICS nations—has become ever more significant. This research delves into the impact of health expenditure, trade openness, and income distribution on health indicators such as infant mortality rate (IMR), life expectancy (LE), and crude death rate (CDR) in BRICS, including Brazil, Russia, India, China and South Africa. The study uses annual time series panel data from 2000 to 2023 and applies the cross-sectional asymmetric autoregressive distributed lag (CS-NARDL) model to examine these relationships. The findings reveal that an increase in health spending leads to reductions in mortality and death rates, while reduced spending has a more pronounced (negative) effect on health indicators. Moreover, the study highlights the organic improvement in health indicators observed in open economies, as they benefit from the exchange of advanced health technology and services. The results indicate that an increase in income among the poorest households in the lowest quartile of income distribution enhances their access to health services, thereby leading to improved health indicators. This study contributes to the existing literature on the impact of health expenditure and income distribution on health indicators. Governments should establish mechanisms to evaluate the effectiveness of healthcare spending on health outcomes, enabling them to improve their healthcare policies and programs.